Biblical Hermeneutics as a Site of Struggle: South African Sites of Contestation in the Late 1980s and Early 1990s - West, Gerald O. (Scriptura, 2025)
‘Hermeneutics’, or the theory of the interpretation of texts, was a substantive component of much biblical scholarship in the 1980 and 1990s. Many articles or essays would begin with a definition of ‘hermeneutics’. Few, however, would be explicit about their own ‘theory of the interpretation of texts’, preferring to define ‘hermeneutics’ and then continue as if their own theory of the interpretation of texts was self-evident. Significantly, South African Black Theology, particularly in its second phase (in the late 1980s), was explicit about its theory of the interpretation of text. Situating itself within this trajectory, the Ujamaa Centre for Community Development and Research has attempted to be explicit about its hermeneutics since its inception in the late 1980s. This article locates the hermeneutic trajectory of the Ujamaa Centre within the formative hermeneutic debates in the late 1980s and early 1990s, drawing on the work of South Africans like Welile Mazamisa (whose work I along with other colleagues celebrate; see 2025-HTS: Honouring Prof Welile Mazamisa: The Reader, the Text, and Two Horizons), Bernard Lategan, Gunther Wittenberg, Jonathan Draper, Itumeleng Mosala, Takatso Mofokeng, and others. The Ujamaa Centre was fortunate at the time, in the early 1990s, in having the inclusive space of Bernard Lategan’s yearly Consultation on Contextual Hermeneutics, facilitated by the Centre for Contextual Hermeneutics at Stellenbosch University, as well as the inclusive publication practice of the journal Scriptura, which published the work of this Consultation and related biblical hermeneutic work. This yearly workshop identified biblical (and theological) hermeneutics as its core focus. My article tracks these formative conversations, reflecting on how this yearly workshop and Scriptura provided the safe space to be overt about the Ujamaa Centre’s emerging theory of the interpretation of texts.